2014
DOI: 10.1007/s12192-014-0521-8
|View full text |Cite
|
Sign up to set email alerts
|

Identification and bioinformatics analysis of microRNAs associated with stress and immune response in serum of heat-stressed and normal Holstein cows

Abstract: MicroRNAs (miRNAs) are small single-stranded non-coding RNAs that have an important regulatory function in animal growth and developmental processes. However, the differential expression of miRNA and the role of these miRNAs in heat-stressed Holstein cows are still unknown. In this study, the profile of differentially expressed miRNAs and the target genes analysis in the serum of heat-stressed and normal Holstein cows were investigated by a Solexa deepsequencing approach and bioinformatics. The data identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
72
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(81 citation statements)
references
References 34 publications
6
72
2
Order By: Relevance
“…Moreover, heat stress also damages cows' immune system of (SalakJohnson and McGlone 2007). Our recent work showed that heat stress significantly increases some miRNAs expression especially miR-181a in Holstein cows, which is related to immune response reactions (Zheng et al 2014).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Moreover, heat stress also damages cows' immune system of (SalakJohnson and McGlone 2007). Our recent work showed that heat stress significantly increases some miRNAs expression especially miR-181a in Holstein cows, which is related to immune response reactions (Zheng et al 2014).…”
Section: Discussionmentioning
confidence: 97%
“…Recent work showed that miR-181a is a multifunctional miRNA that participates in many biological processes, such as apoptosis, cell proliferation, cellular invasion, and tumor suppression (Korhan et al 2014). Our recent study suggested that miR-181a is highly expressed in the serum of heat-stressed Holstein cows by a Solexa deep-sequencing approach, and is even involved in stress and immune responses (Zheng et al 2014). However, within the mechanism of down-regulation of miR-181a in heat-stressed Holstein cows, PBMCs' damage has not been reported to date.…”
Section: Introductionmentioning
confidence: 97%
“…miR‐2284 and miR‐2285 are bovine‐specific families without homologues in humans or mice . Although the family members have been detected in different bovine organs, including the liver, rumen, jejunum , mammary gland , milk components , and serum , their precise functions remain largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that miRNAs are exported to the extracellular environment through microvesicles such as exosomes and circulate in the blood [18, 19] and have shown tremendous potential as non-invasive biomarkers in human cancers [2022] and pregnancy [23], estrus [24], and aging [17] in dairy cattle. In addition, miRNAs have different expression patterns under environmental and physiological changes such as HS [25, 26]. The goal of this study was to find the potential biomarkers related to HS in lactating dairy cows and to identify the association of candidate miRNAs with putative targeted genes under HS.…”
Section: Introductionmentioning
confidence: 99%